Synthesis of novel diene polymer via friedel–crafts‐type reaction of polybutadiene with aromatic compounds. Issue 7 (14th February 2019) - Shinke, Yu
ABSTRACT: This study describes a novel and facile synthesis strategy for a styrene‐butadiene rubber (SBR)‐like polymer via Friedel–Crafts‐type reaction between aromatic compounds and polybutadiene using an aluminum chloride as a catalyst. Although gelation was induced by a reaction of a generated carbocation with olefins in other polybutadiene chains in benzene and toluene because of their low electron densities on their rings, anisole with a higher electron density reacted with the polybutadiene carbocation efficiently. The introduction ratio of anisole increased as the reaction proceeded, and the obtained polymer, BRAN polymer, contained 15% anisoles for olefins in the polybutadiene in 4 h at 80 °C as estimated by 1 H NMR analysis. The glass‐transition temperature ( T g ) of the BRAN polymer also increased with anisole content ( T g ~−50 °C when anisole contents 20%). The vulcanizate containing the BRAN polymer showed higher mechanical properties compared to samples using other matrix polymers. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2019, 57, 841–847 Abstract : An efficient synthesis of an SBR‐like polymer was achieved via Friedel–Crafts‐type reaction of BR with aromatic compounds. The gelation was competitive to the Friedel–Crafts reaction with benzene and toluene because of their low electron densities. A generated carbocation on the BR chain reacted predominantly with anisole having a higher electron density. The glass transition temperature increased with increasing anisole content (−50 °C at 20% anisole). The aromatic‐modified BR enhanced the mechanical properties of BR.